(untitled) (Bioscience Journal, 2017)
The study exposed in this paper aimed at evaluating the influence of light, temperature and presence or absence of mesocarp in seeds on the germination of Euterpe edulis Mart. (juçara-palm). The germination of seeds with and without mesocarp was assessed in the presence of light (12 h photoperiod) or in the darkness, and at temperatures of 25, 28 or 30C. A complete randomized 2x2x3 (mesocarp presence, light conditions and temperatures) factorial design was used. The seed germinability and the Germination Speed Index (GSI) were evaluated. Seeds of E. edulis were indifferent either to the presence of light or to temperatures of 25, 28 and 30C. The germinability of the seeds with mesocarp was lower (6 to 10%) than those without mesocarp (47 to 75%).